Characterization of Aerosol Hygroscopicity Over the Northeast Pacific Ocean: Impacts on Prediction of CCN and Stratocumulus Cloud Droplet Number Concentrations. Issue 7 (3rd July 2020) - Schulze, B. C.; Charan, S. M.; Kenseth, C. M.; Kong, W.; Bates, K. H.; Williams, W.; Metcalf, A. R.; Jonsson, H. H.; Woods, R.; Sorooshian, A.; Flagan, R. C.; Seinfeld, J. H.
Abstract: During the Marine Aerosol Cloud and Wildfire Study (MACAWS) in June and July of 2018, aerosol composition and cloud condensation nuclei (CCN) properties were measured over the N.E. Pacific to characterize the influence of aerosol hygroscopicity on predictions of ambient CCN and stratocumulus cloud droplet number concentrations (CDNC). Three vertical regions were characterized, corresponding to the marine boundary layer (MBL), an above‐cloud organic aerosol layer (AC‐OAL), and the free troposphere (FT) above the AC‐OAL. The aerosol hygroscopicity parameter ( κ ) was calculated from CCN measurements ( κ CCN ) and bulk aerosol mass spectrometer (AMS) measurements ( κ AMS ). Within the MBL, measured hygroscopicities varied between values typical of both continental environments ( 0.2) and remote marine locations ( 0.7). For most flights, CCN closure was achieved within 20% in the MBL. For five of the seven flights, assuming a constant aerosol size distribution produced similar or better CCN closure than assuming a constant "marine" hygroscopicity ( κ = 0.72). An aerosol‐cloud parcel model was used to characterize the sensitivity of predicted stratocumulus CDNC to aerosol hygroscopicity, size distribution properties, and updraft velocity. Average CDNC sensitivity to accumulation mode aerosol hygroscopicity is 39% as large as the sensitivity to the geometric median diameter in this environment. Simulations suggest CDNC sensitivity to hygroscopicity is largest in marine stratocumulus with low updraft velocities (<0.2 m s −1 ), where accumulation mode particles are most relevant to CDNC, and in marine stratocumulus or cumulus with large updraft velocities (>0.6 m s −1 ), where hygroscopic properties of the Aitken mode dominate hygroscopicity sensitivity. Key Points: Aerosol hygroscopicity exhibited substantial temporal variability in the MBL Errors in predicted MBL CCN concentrations produced by assuming a constant aerosol size distribution or hygroscopicity are discussed Sensitivity of simulated CDNC to hygroscopicity is maximized in marine clouds with either very weak or relatively strong updraft velocities